Correlation between Antiviral and Steroid Therapies, COVID-19 Severity, and patient Outcomes: A Cross-Sectional Study - Urfa Tabassum Kayani, Santosh Kumar Sidhwani, Ambrina Khatoon, Ashok Kumar, Talat Mirza, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To investigate the relationship between the severity of COVID-19 and the impact of antiviral medications, specifically Remdesivir, and steroid treatments on disease outcomes. Study design and setting: A cross-sectional study involving 103 COVID-19 patients was conducted at Ziauddin University's outpatient departments (OPDs), inpatient facilities and intensive care units (ICUs) during the years 2021 and 2022. Methodology: Patients who tested positive for COVID-19 through PCR testing were included in the study. SARS-CoV-2 RNA was detected through qualitative RT-PCR, and data were retrieved from medical records, encompassing demographic, clinical, and laboratory details. The impact of antiviral and steroid treatments on disease severity and outcomes was analyzed using SPSS for statistical analysis. Ethical considerations were paramount, with measures including obtaining informed consent and securing approval from the Ethical Review Committee (ERC). Results: Remdesivir use correlated with lower severity and higher discharge rates (p < 0.001); steroids were associated with improved discharge rates (p = 0.037). Younger age (≤50 years) related to milder cases (p = 0.003), and dyspnea indicated increased severity (p = 0.001). Comorbidities were associated with a higher likelihood of severe outcomes (p = 0.009). Fever and cough, common symptoms, were not significant predictors. Various lab markers showed no significant associations with COVID-19 severity. Conclusion: Antiviral and steroid therapies, especially Remdesivir, show promise in mitigating COVID-19 severity and improving outcomes. Larger prospective studies are needed for validation in this ongoing global health emergency. Keywords: Antiviral, Remdesivir, RT-PCR, SARS-CoV-2, Steroid